Fabrication of 7.2% Efficient CZTSSe Solar Cells Using CZTS Nanocrystals - Guo, Qijie; Ford, Grayson M; Yang, Wei-Chang; Walker, Bryce C; Stach, Eric A; Hillhouse, Hugh W; Agrawal, Rakesh (Journal of the American Chemical Society, 2010)
Earth abundant copper-zinc-tin-chalcogenide (CZTSSe) is an important class of material for the development of low cost and sustainable thin film solar cells. The fabrication of CZTSSe solar cells by selenization of CZTS nanocrystals is presented. By tuning the composition of the CZTS nanocrystals and developing a robust film coating method, a total area efficiency as high as 7.2% under AM 1.5 illumination and light soaking has been achieved.